The tea party movement - Kumar, Anup (Javnost (Ljubljana), 2011)
This critical essay is an attempt to understand populist discourse of the Tea Party movement and the lurking reactionary- nationalism in the background. Taking a discourse theoretic approach proposed by Laclau (2005), the essay attempts to show how the differential issues/discontents in the populist discourse of the Tea Party came to share equivalence through the articulation of equivalential social logic and the shared universal negative feature in thekey signifiers and the antagonism to the government and the incumbents. Theessay problematises the conceptualisation of populism as a form of political practice that speaks for the people and against the established power structures, and argues that populism must be critically analysed as a discursive political practice independent of ideology or content.
Keywords: United States of America; ZDA; javnost; sociologija politike; analiza diskurza; politična desnica; nacionalizem; nationalism; populizem